Design of Multimode Interference Optical Splitter Based on BenzoCyclobutene (BCB 4024-40) Polymer - Ibrahim, Mohd Haniff; Mohd. Kassim, Norazan; Mohammad, Abu Bakar; Chin, Mee-Koy (School of Postgraduate Studies, UTM, 2006)
1x2 and 1x3 planar optical splitter based on BenzoCyclobutene (BCB 4024-40) polymeric material are proposed. The design is based on symmetric interference mechanism and simulated using the combined technique of effective index method and commercial BPM-CAD software from Optiwave. A ridge waveguide of BCB 4024-40 on BK7 glass substrate is employed as the simulated structure. The simulation at 1550 nm optical wavelength shows an insertion loss of 2.75 dB and 4.73 dB for 1x2 and 1x3 splitter respectively. The uniformity is shown to be less than 0.5 dB. This provides useful idea on the applicability of BCB 4024-40 to be realized as an optical splitter.